EFFECTIVE WAYS TO PREPARE CHILDREN WITH PRESCHOOL SPEECH DEFICIENCIES FOR SCHOOL EDUCATION - Makhmudova Madinakhan Sobirkhanovna; Khaydarova Umidakhan Bakhromjonovna (Galaxy International Interdisciplinary Research Journal, 2024)
The goal of preschool education is to form a child's personality in a healthy and mature manner, prepared for school in accordance with the State requirements for the education of children of preschool age.